Foliar water uptake in Amazonian trees: Evidence and consequences - Oliver Binks; Maurizio Mencuccini; Lucy Rowland; Antonio C. L. da Costa; Claudio José Reis de Carvalho; Paulo Bittencourt; Cleiton Eller; Grazielle Sales Teodoro; Eduardo Jorge Maklouf Carvalho; Azul Soza; Leandro Ferreira; Steel Silva Vasconcelos; et al. (Global Change Biology, 2019)
The absorption of atmospheric water directly into leaves enables plants to alleviate the water stress caused by low soil moisture, hydraulic resistance in the xylem and the effect of gravity on the water column, while enabling plants to scavenge small inputs of water from leaf‐wetting events. By increasing the availability of water, and supplying it from the top of the canopy (in a direction facilitated by gravity), foliar uptake (FU) may be a significant process in determining how forests interact with climate, and could alter our interpretation of current metrics for hydraulic stress and sensitivity. FU has not been reported for lowland tropical rainforests; we test whether FU occurs in six common Amazonian tree genera in lowland Amazônia, and make a first estimation of its contribution to canopy–atmosphere water exchange. We demonstrate that FU occurs in all six genera and that dew‐derived water may therefore be used to “pay” for some morning transpiration in the dry season. Using meteorological and canopy wetness data, coupled with empirically derived estimates of leaf conductance to FU ( k fu ), we estimate that the contribution by FU to annual transpiration at this site has a median value of 8.2% (103 mm/year) and an interquartile range of 3.4%–15.3%, with the biggest sources of uncertainty being k fu and the proportion of time the canopy is wet. Our results indicate that FU is likely to be a common strategy and may have significant implications for the Amazon carbon budget. The process of foliar water uptake may also have a profound impact on the drought tolerance of individual Amazonian trees and tree species, and on the cycling of water and carbon, regionally and globally.